PENGARUH PERTUMBUHAN PERUSAHAAN, LIKUIDITAS, DAN MATURITY TERHADAP PERINGKAT OBLIGASI PERUSAHAAN DI BURSA EFEK INDONESIA - Sirma Nila Sucipta, Ni Kadek; Rahyuda, Henny (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
The purpose of this study was to determine the effect of companies growth, companies liquidity and bond maturity towards the bond rating from PT. PEFINDO in Indonesia Stock Exchange (IDX) 2009-2012. This study used a non-participant  observation method by analyzing financial statements and corporate bond data which published on the official website of the Stock Exchange (www.idx.co.id). The sample was 15 companies which are taken by purposive sampling method. The data analysis technique used is logistic regression. The results of this study indicate that companies growth, companies liquidity and bond maturity partially positive and significant impact on the ratings of bonds issued by PT. PEFINDO on the Indonesia Stock Exchange        2009-2012.
Keywords: companies growth, companies liquidity and bond maturity